1998
DOI: 10.1038/sj.bjp.0702114
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel selective hypotensive vasopressin peptides that exhibit little or no functional interactions with known oxytocin/vasopressin receptors

Abstract: 1 Arginine-vasopressin (VP) has both vasoconstricting and vasodilating action. We report here the discovery of four novel selective hypotensive VP analogues: d (CH 2 2 Bioassays in rats for activities characteristic of neurohypophysial peptides showed that the four VP peptides possessed little or no V 1a , V 2 or oxytocin (OT) receptor agonistic or antagonistic activities. 3 In anaesthetized rats, these peptides (0.05 ± 0.10 mg kg 71 i.v.) elicited a marked fall in arterial blood pressure. 4 Blockade of chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…The results suggested that position 3 is important not only for binding and recognition, but also for the intrinsic activity (14). In subsequent studies of other authors, Arg 3 /Phe 3 interchange in the nonselective antagonist mentioned above, [Cpa 1 , d ‐Tyr(Et) 2 , Val 4 ]AVP, resulted in a series of novel, selective hypotensive vasopressin analogues (15). Furthermore, another investigation of position 3 in AVP substituted with aliphatic, aromatic, conformationally restricted, polar and charged amino acids suggests that only thienylalanine (Thi) and aliphatic amino acids are well tolerated to give analogues with appreciable retention of activity (16).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that position 3 is important not only for binding and recognition, but also for the intrinsic activity (14). In subsequent studies of other authors, Arg 3 /Phe 3 interchange in the nonselective antagonist mentioned above, [Cpa 1 , d ‐Tyr(Et) 2 , Val 4 ]AVP, resulted in a series of novel, selective hypotensive vasopressin analogues (15). Furthermore, another investigation of position 3 in AVP substituted with aliphatic, aromatic, conformationally restricted, polar and charged amino acids suggests that only thienylalanine (Thi) and aliphatic amino acids are well tolerated to give analogues with appreciable retention of activity (16).…”
Section: Introductionmentioning
confidence: 99%
“…More recent reports on such analogues resulted in inconsistent information, on one hand supporting the conclusion that this position is intolerant to structural modifications [5][6][7][8] and on the other hand demonstrating that Phe 3 could be replaced by a variety of amino acids with appreciable retention of activity. [7][8][9] In 1997 we described AVP analogues modified in position 3 with β-(1-naphthyl)-L-alanine. The results suggested that position 3 was important not only for binding and recognition but also for intrinsic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Early findings demonstrating that aromatic Phe 3 is important for vasopressor activity, whereas aliphatic Ile 3 is crucial for oxytocic activity, probably influenced the design of neurohypophyseal hormone analogues because initially only a few studies were undertaken that involved substitutions in position 3 of AVP. More recent reports on such analogues resulted in inconsistent information, on one hand supporting the conclusion that this position is intolerant to structural modifications and on the other hand demonstrating that Phe 3 could be replaced by a variety of amino acids with appreciable retention of activity. In 1997 we described AVP analogues modified in position 3 with β-(1-naphthyl)- l -alanine. The results suggested that position 3 was important not only for binding and recognition but also for intrinsic activity .…”
Section: Introductionmentioning
confidence: 99%
“…The development of receptor‐selective analogues of neurohypophysial peptide hormones has facilitated the characterization of receptor subtypes and provided tools to address the diverse roles of these important peptide mediators. Moreover, the recent description of novel hypotensive vasopressin peptides (Chan et al ., 1998) and the development of chimeric vasopressin analogues (Howl et al ., 1997) indicate new avenues for structurally modified vasopressin analogues. Thus, modifications to improve receptor‐selectivity and/or stability and optimise pharmacodynamic and pharmacokinetic properties could enhance the utility and therapeutic potential of vasopressin/oxytocin analogues.…”
Section: Discussionmentioning
confidence: 99%